Uczniowie z doświadczeniem migracji na lekcjach języka niemieckiego w polskiej szkole podstawowej – perspektywa nauczycieli - Janicka, Monika (Neofilolog, 2024)
In February 2022, the invasion of Ukrainian territories by Russian forces took place, leading to a mass exodus of the Ukrainian population from the war-affected areas. Many individuals who left Ukraine due to the war sought refuge in Poland, and their children began attending Polish schools. Some of these children appeared in Polish classes only temporarily, but as reported by the Ministry of Education and Science in September 2023, 180,000 students from Ukraine began their education in Polish schools. The influx of Ukrainian children into Polish schools posed various challenges, especially for foreign language teachers, as their classes became linguistically and culturally heterogeneous. The aim of the conducted study was to answer the following questions: (1) What kind of challenges do German language teachers face in classes where students from Ukraine are learning? (2) Which teaching techniques do German language teachers consider most effective in linguistically and culturally heterogeneous classes? The article presents the results of the study conducted through interviews using an unstructured dialogical method with four German language teachers teaching elementary school students with migration experience. The research framework was based on the concept of Universal Design for Learning, taking into account the principles of inclusive teaching.